2021
DOI: 10.1111/rsp3.12425
|View full text |Cite
|
Sign up to set email alerts
|

A Geospatial Analysis of Temporary Housing Inequality among Socially Marginalized and Privileged Groups in India

Abstract: A major obstruction of Indian society to establish equality, balanced growth and development is regional and social group‐wise inequality in availing even basic human needs as well as housing conditions. The present study focuses on mapping the nationwide spatial disparity in the distribution and inequality of temporary housing among socially marginalized and privileged groups, along with three administrative hierarchies: National–State–District. Varieties of measures (Lorenz curve, Gini coefficient, correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…India is a nation with regional disparity and diversity. Several researchers previously studied regional variations in different aspects like human and socioeconomic development (Bakshi et al, 2015; Ghosh, 2018; Ghosh et al, 2021; Jose, 2019; Kundu et al, 2013; Roy, 2012). Previously, Chaudhuri et al (2020) outlined the concentration of households with good WASH infrastructure, including safe drinking water, drainage, and latrine facilities, in western coastal districts and north Indian districts situated in the capital city Delhi and its adjacent states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…India is a nation with regional disparity and diversity. Several researchers previously studied regional variations in different aspects like human and socioeconomic development (Bakshi et al, 2015; Ghosh, 2018; Ghosh et al, 2021; Jose, 2019; Kundu et al, 2013; Roy, 2012). Previously, Chaudhuri et al (2020) outlined the concentration of households with good WASH infrastructure, including safe drinking water, drainage, and latrine facilities, in western coastal districts and north Indian districts situated in the capital city Delhi and its adjacent states.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Das and Mistri (2013), based on Census of India, 2011 data, highlighted the poor condition of housing quality, basic housing amenities, and overall household quality of living among eastern Indian states. Later, Ghosh et al (2021) showed a relatively higher concentration of temporary housing in the eastern coastal area, eastern, and central Indian states like Odisha, Jharkhand, Bihar, Uttar Pradesh, and some parts of Madhya Pradesh and West Bengal. Several researchers have revealed a lower level of human development (Suryanarayana et al, 2011) and other socioeconomic development (Jose, 2019; Kundu et al, 2013) in those districts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,000 and above farmer credit card limit along with per‐head income level determining the economic capital of the villages. In addition, better shelter conditions, household's WASH facilities are linked with social dignity and healthy living, enhancing adaptive capacity during environmental hazards (Ghosh, Alam, et al, 2021; Ghosh, Hossain, & Alam, 2021; Ghosh, Saha, & Cartone, 2021; Patidar, 2019). Therefore, to outline security of livelihood, we considered good housing conditions, good wall, floor and roof condition, adequate dwelling rooms, and electricity as determining shelter condition.…”
Section: Methodsmentioning
confidence: 99%